Factors affecting turnover intention among Gen Y in hotel industry / Mohamad Niza Md Nor ... [et al.] - Md Nor, Mohamad Niza; Mat Noor, Ahmad Nizan; Ahmad, Zulaiha; Khalid, Shaiful Annuar; Ibrahim, Ima Ilyani (Universiti Teknologi MARA, Perlis, 2017)
Employing and retaining the best employees is a vital process to organizational success. Organizations that can effectively retain their workforces may strengthen their competitive advantage over organizations that cannot. Employee turnover is very costly and has become a crucial factor that can affect the organizational overall performance. Although studies on turnover intention has become a phenomenon in organizational research, restudying this phenomenon is vital in order to further understand factors that affecting employees' turnover intention. This study examines work value, quality of work life and safety as predictors of employee turnover intention among Gen Y employees working in hotel industry in Malaysia. 110 usable questionnaires were used in statistical analyses. The results indicated that all predictors have significant relationship with employee turnover intention. Finally, implication to body of knowledge, practitioners and future studies are discussed